Profile and health conditions of people from ageing program, by the nursing view - Rosa Aparecida Pavan Bison; Antonia Regina F. Furegato; Vanessa Pellegrino Toledo (Rev Rene)
The populational aging in Brazil is a concern of government authorities and health professionals. The present work aimed at knowing the profile and health conditions of old people in Araras city. The 146 elderly people from the Council Ageing Program were assisted through nursing appointment based on a schedule from the Human Answer Model and Nursing Diagnosis standardization by NANDA. The results allowed to trace this population’s profile. The detection of the necessities of oral and dental treatment resulted in their inclusion in programs (prosthesis, preventive and integrated) offered by the Dentristy College. Another result was the direction of such clients to groups according to their common interest and needs in other programs in the University, such as Nutrition, Sexuality, Diabetes and Blood Pressure.